Ultrasound-Assisted Enzymatic Extraction of the Active Components from Acanthopanax sessiliflorus Stem and Bioactivity Comparison with Acanthopanax senticosus - Qiaomu You; Yanjun Ren; Jiaotong Li; Guangnian Zeng; Xiongfei Luo; Chunying Zheng; Zhonghua Tang (Molecules)
Acanthopanax senticosus (ASC) contains a variety of bioactive compounds and serves as an important traditional Chinese medicinal resource. However, its prolonged growth cycle and reliance on wild populations limit its practical use. To explore the potential of Acanthopanax sessiliflorus (ASF) as an alternative, this study focused on optimizing the extraction process and assessing the bioactivity of stem extracts. The Analytic Hierarchy Process-Entropy Weight Method (AHP-EWM) was applied to comprehensively score five key active compounds in ASF stems, establishing a benchmark for evaluating extraction efficiency. Ultrasound-assisted enzymatic extraction (UAEE) was employed, and orthogonal and response surface experiments were conducted to refine the extraction parameters. The optimal conditions identified were an ultrasound temperature of 59 °C, a duration of 57 min, an ethanol concentration of 61%, and a liquid-to-material ratio of 39:1, resulting in an AHP-EWM composite score of 94.76. Comparative analysis of antibacterial and antioxidant activities revealed that ASC extracts exhibited superior antibacterial effects, while ASF extracts demonstrated enhanced antioxidant properties. These findings support the partial replacement of ASC with ASF, contributing to the conservation of wild resources and expanding the application of ASF in medicinal development.